Liquidity in immune cell signaling - Dustin, M; Muller, J (American Association for the Advancement of Science, 2016)
Signaling molecules (blue) form liquid-like phases, instead of static aggregates, in a reconstituted system using an artificial lipid bilayer. Shown is a model of clustered pLAT and associated signaling molecules that phase separate into a liquid-like droplet in response to TCR activation. The cluster induces actin polymerization, which is a solid phase gel that changes the shape of the liquid-like droplet.